THEORETICAL FRAMEWORK FOR LAND CAPITAL MANAGEMENT OF FARMS - HUTOROV, Andrii; GROSHEV, Serhii; GROSHEV, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The efficiency of farmers’ management significantly depends on the effective management of land capital. It has been established that the management of land capital of farms is a system that covers all social relations and generally determines the set of relationships between the elements of the management system aimed at the rational and environmentally responsible land use. The subsystems of land capital management of farms are economic, environmental, regulatory, administrative, innovation and management, and land management and technological. The structural model of the system of land capital management of farms includes the subject, object, subject matter, purpose, goals, principles, functions, methods and mechanisms of management. The subject of this system, i.e., the management subsystem, are farms and government authorities of all levels that implement the state land, agrarian and tax policies and supervise compliance with the norms of rational land use. The object of management is differentiated by the depth of the essential content of the definition of “land”, covering land and its fertility, land resources and their capitalization, land and its investment attractiveness, agricultural land (by type) and the efficiency of its usage. The economic interests of landowners, land users, the state, and society are the basis for making managerial decisions by a farmer. It has been shown that the system of land capital management of farms should be based on the following basic principles: systematicity; purposefulness; balance of interests of a farmer, landowners, the state and society in the use of land resources; payment for land use; sustainable development of agricultural land use; rationality and economic feasibility of land use; priority of land protection as the main means of production; responsibility and information. The functions of land capital management of farms include planning of land capital use; forecasting of land capital use in the short, medium and long term; organization of land capital use; motivation and control of rational use of land capital.